2011
DOI: 10.1089/jmf.2010.0327
|View full text |Cite
|
Sign up to set email alerts
|

Gnetum africanum: A Wild Food Plant from the African Forest with Many Nutritional and Medicinal Properties

Abstract: Gnetum africanum is a forest liana that grows abundantly in Central Africa, South America, and tropical and subtropical Asia. Its leaves are eaten as a vegetable, either raw or finely chopped and cooked; they are also widely used as an ingredient in soups and stews and are much in demand for their nutritional and therapeutic properties. In the latter application, various fractions of G. africanum are used medicinally to treat many different illnesses. Many studies have also shown that the chemical composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 15 publications
2
50
0
Order By: Relevance
“…Although G. africanum has been reported to contain anti-nutritional and toxic components, they occur at levels below their toxicity thresholds. Ali, Assanta and Robert [13] reported that whereas the toxicity level for hydrocyanic acid is 35 mg/10 g dry matter, the level of this acid in the leaves of this plant is only 0-5.4 mg/100g. Also for oxalate to be toxic, it must be present in concentrations of the order of 2-5 g/100 g dry matter, whereas in G. africanum concentrations of 16-68 mg/100 g DM were detected [13].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Although G. africanum has been reported to contain anti-nutritional and toxic components, they occur at levels below their toxicity thresholds. Ali, Assanta and Robert [13] reported that whereas the toxicity level for hydrocyanic acid is 35 mg/10 g dry matter, the level of this acid in the leaves of this plant is only 0-5.4 mg/100g. Also for oxalate to be toxic, it must be present in concentrations of the order of 2-5 g/100 g dry matter, whereas in G. africanum concentrations of 16-68 mg/100 g DM were detected [13].…”
Section: Discussionmentioning
confidence: 96%
“…Ali, Assanta and Robert [13] reported that whereas the toxicity level for hydrocyanic acid is 35 mg/10 g dry matter, the level of this acid in the leaves of this plant is only 0-5.4 mg/100g. Also for oxalate to be toxic, it must be present in concentrations of the order of 2-5 g/100 g dry matter, whereas in G. africanum concentrations of 16-68 mg/100 g DM were detected [13]. However, many toxicity studies on Gnetum africanum in the literature were done using 3-30-day toxicity tests [25][26][27].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…They are collected in the wild rather than cultivated throughout tropical Africa. The Asutan variety is very rich in crude fibers [50], [51].…”
Section: Discussionmentioning
confidence: 99%
“…Most wild foods available in markets throughout the country originate from the forest zone. For example, leafy green vegetables are "mainstays in the diets of rural and urban households across most of Africa" more generally, and are especially important in Central Africa [133][134][135]. Wild leafy vegetables may be the major source of micronutrients for the majority of resource-poor people throughout the region [12,71,135,136].…”
Section: Adequacymentioning
confidence: 99%